2006
DOI: 10.1097/01.mat.0000227680.67901.01
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Two On-Line Reversed Line Position Hemodialysis Vascular Access Flow Measurement Techniques: Saline Dilution and Thermodilution

Abstract: Periodical access flow measurements can predict the development and presence of vascular access flow-limiting stenosis and subsequent thrombosis. Access flow measurement has become a standard in vascular access care. Different techniques to measure access flow are available. The aim of this study was to compare an integrated access flow measurement device, based on thermodilution (Blood Temperature Monitor, BTM, Fresenius Medical Care, Bad Homburg, Germany), with the gold standard, the HD01 (Transonic Systems … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 14 publications
2
26
1
1
Order By: Relevance
“…While different studies compared the available techniques [9,10,12,[14][15][16] , none of them investigated to which degree the prescribed recommendations for performing measurements should be followed. Therefore, besides the comparison of three AF measuring methods (based on US, BTM, and OCM), the present study investigated whether US and BTM measurements are influenced by the Q B applied, the time point of measurement, and the patient's position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While different studies compared the available techniques [9,10,12,[14][15][16] , none of them investigated to which degree the prescribed recommendations for performing measurements should be followed. Therefore, besides the comparison of three AF measuring methods (based on US, BTM, and OCM), the present study investigated whether US and BTM measurements are influenced by the Q B applied, the time point of measurement, and the patient's position.…”
Section: Discussionmentioning
confidence: 99%
“…Two modules available on several hemodialysis machines, i.e. the blood temperature monitoring (BTM) [8][9][10] and online clearance monitoring (OCM) [11,12] , however, have also been used to calculate AF.…”
Section: Introductionmentioning
confidence: 99%
“…This indirect dilution method detects early fistula dysfunction by percentage of access recirculation with a diagnostic sensitivity of 81.8% and a specificity of 98.6% [29]. The mean values obtained with thermodilution in recent studies that included mostly patients with AVF were 1,034 ml/min and 1,170 ml/min with no significant difference with respect to the SDM and Delta-H methods, respectively [30,31]. In the present study, BTM-Qa showed better general accuracy and concordance than OLC-Qa compared with the ultrasonography method.…”
Section: Discussionmentioning
confidence: 99%
“…All referrals for intervention were based on standard Kidney Disease Outcomes Quality Initiative (KDOQI)/Fistula First published criteria, which may include one or a combination of the following: physical examination abnormalities, poor blood flows, elevated venous/arterial pressures, increased bleeding, inability to cannulate, decrease in Transonic HD02 Hemodialysis Monitor (Transonic Systems, Ithaca, NY) access flows, or decrease in dialysis adequacy measured by Kt/V or URR (25,26).…”
Section: Technical Descriptionmentioning
confidence: 99%
“…Patients had their access blood flow and URR measured by Transonic HD02 from day 1 to day 30 after intervention and then routinely as part of our access monitoring program once per month (25,26 …”
Section: Technical Descriptionmentioning
confidence: 99%